2020
DOI: 10.1021/acsomega.9b03908
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Coarse-Grained Modeling to Characterize and Optimize Dendrimer-Based Nanocarriers for Short Interfering RNA Delivery

Abstract: Dendrimer nanocarriers are unique hyper-branched polymers with biomolecule-like properties, representing a promising prospect as a nucleic acid delivery system. The design of effective dendrimer-based gene carriers requires considering several parameters, such as carrier morphology, size, molecular weight, surface chemistry, and flexibility/rigidity. In detail, the rational design of the dendrimer surface chemistry has been ascertained to play a crucial role on the efficiency of interaction with nucleic acids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…By an increase of the standard deviation, due to the increment of copolymers, it is reasonable to hypothesize that the presence of several polycations leads to competition phenomena to bind to the interaction sites. When copolymers are present, (i.e., N/P ratio > 1), competition mechanisms can change certain thermodynamic parameters [ 17 ], including the stoichiometric number and the enthalpy, thus explaining a visible decrease in ΔH. These competition phenomena suggest a greater instability of the system and a challenge to maintaining a point of charge-neutralization, which may ultimately hinder efficient cell transfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By an increase of the standard deviation, due to the increment of copolymers, it is reasonable to hypothesize that the presence of several polycations leads to competition phenomena to bind to the interaction sites. When copolymers are present, (i.e., N/P ratio > 1), competition mechanisms can change certain thermodynamic parameters [ 17 ], including the stoichiometric number and the enthalpy, thus explaining a visible decrease in ΔH. These competition phenomena suggest a greater instability of the system and a challenge to maintaining a point of charge-neutralization, which may ultimately hinder efficient cell transfection.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the initial conformation of the PLL moiety was obtained from the PEPFOLD-3 server [ 14 ]. Partial charges of the triblock copolymer were obtained using the AM1-BCC method [ 15 ], widely used in the field of polymer partial charge calculation [ 11 , 16 , 17 ]. The general amber force field (GAFF) [ 18 ] was chosen to describe the siRNA and the triblock copolymer molecules.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this problem, the Coarse-Grained (CG) models are designed to perform MD simulations for large time scales in order to realistically describe the physical characteristics of these biological systems [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. We note that up until now, the coarse-grained modeling of only relatively small DNA systems has been performed by using the Martini force field where the six to seven CG interaction sites are taken into account [ 22 , 23 ], and a similar progress has been made for RNA systems [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RNA systems can be used as one of the best vehicles for drug delivery because it is compatible with the human body. Hence, the development and detailed analysis of all-atom molecular dynamics simulations and coarse-grained models of RNA nanotubes become imperative [ 8 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. This is also important in the light of existing challenges in the development of RNA therapeutic methodologies, including the delivery to target cells and stability issues in blood/tissues which are subject of intensive discussions in the literature [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used in biomedical fields such as drug delivery, gene therapy, medical imaging and diagnosis, which are one of the most promising nanocarriers. [6][7][8]Recent studies have found that PAMAM itself has some biological activities and functions. For example, Chauhan et al.…”
mentioning
confidence: 99%